Atypical Osteomyelitis Caused by Mycobacterium chelonae—A Multimodal Imaging Approach. (31st March 2013) - Talanow, Roland; Vieweg, Hendryk; Andresen, Reimer
Abstract : We present an unusual case of a biopsy-proven Mycobacterium chelonae infection (MCI) of skin and soft tissue, which led to osteomyelitis in a 55-year-old Caucasian male. We provide clinical data and discussion about MCI and its diagnostic workup and demonstrate comprehensive imaging findings, including clinical pictures, radiographs, three-phase bone scintigraphy, and combined SPECT/CT findings of this entity, which have not yet been presented in the medical literature.